Genome Sequence of the Bacterioplanktonic, Mixotrophic Vibrio campbellii Strain PEL22A, Isolated in the Abrolhos Bank - Amaral, Gilda Rose S. (American Society for Microbiology, 2012)
Vibrio campbellii PEL22A was isolated from open ocean water in the Abrolhos Bank. The genome of PEL22A consists of 6,788,038 bp (the GC content is 45%). The number of coding sequences (CDS) is 6,359, as determined according to the Rapid Annotation using Subsystem Technology (RAST) server. The number of ribosomal genes is 80, of which 68 are tRNAs and 12 are rRNAs. V. campbellii PEL22A contains genes related to virulence and fitness, including a complete proteorhodopsin cluster, complete type II and III secretion systems, incomplete type I, IV, and VI secretion systems, a hemolysin, and CTXΦ.